(untitled) (Research, Society and Development, 2025)
Photosensitization in cattle is a dermatological condition induced by the interaction between ultraviolet (UV) rays and photosensitizing substances present in certain plants. The Amazon region, characterized by its vast phytobotanical diversity, is home to numerous species with phototoxic potential, capable of triggering photosensitizing reactions in ruminants, especially cattle. The ingestion of these plants leads to the bioaccumulation of compounds such as furanocoumarins, pyrrolizidine alkaloids, saponins and photodynamic chlorophyll derivatives, which, when activated by sunlight, induce phototoxic skin lesions, predominantly in depigmented areas with less hair coverage. This study aims to discuss the main toxic plants present in the Amazon responsible for this condition in cattle, through a literature review. Through the literature review, several plants that contain photosensitizing substances in cattle were identified Brachiaria spp., Crotalaria spp., Enterolobium spp., Jatropha spp., Lantana spp., Mimosa spp., Ricinusspp.,Senna spp. and Senecio spp. Species of the genus Brachiaria are the main responsible for cases of photosensitization in animals, due to their greater prevalence in the North region. The study points to the importance of knowing the characteristics of each plant, the toxic part of each, the clinical signs, performing earlydiagnosis,controlling the animal’s diet, treatment and prevention through adequate pasture management. The scientific literature highlights the need for more research on the impact of these plants on cattle herds, with the aim of promoting more ffective management and prevention practices for these pathologies.